2015
DOI: 10.1055/s-0034-1394465
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Intermittent Running from a Single-visit Field Test

Abstract: Abstract:This study assessed whether the distance-time relationship could be modeled to predict time to exhaustion (TTE) during intermittent running. Thirteen male distance runners (age: 33±14yrs) completed a field test and three interval tests on an outdoor 400m athletics track.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 19 publications
2
24
0
Order By: Relevance
“…6,7,9]. Modelling the depletion and repletion of D´ could help coaches and practitioners to predict the termination of exercise more accurately [15] whilst also be useful for pacing strategies [37]. Today's technology is furthermore able to estimate depletion and reconstitution of D´ during exercise in real time (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…6,7,9]. Modelling the depletion and repletion of D´ could help coaches and practitioners to predict the termination of exercise more accurately [15] whilst also be useful for pacing strategies [37]. Today's technology is furthermore able to estimate depletion and reconstitution of D´ during exercise in real time (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, the duration of the respective predictive runs were not matched in the latter study, what has been shown to affect the parameter estimates [ 12 ]. The reason for the high day-to-day variation of W´ is still unclear and questions on whether W´ can be accurately determined using the power-duration relationship, and if the estimated W´ equals ‘physiological’ W´ , remains to be elucidated [ 12 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the first author (P.F.S.) has analyzed data from professional cyclists and triathletes and observed τ W′ values slower than those predicted by either Skiba et al 21 or Bartram et al 30 In another study, Galbraith et al 31 attempted to model running by using the mean τ W′ value measured for cycling in the heavy domain, 21 concluding that the W′ BAL-INT model was unable to accurately model intermittent running performance. They were more successful when they fit the equation to the runner's data.…”
Section: The W′ Bal Modelsmentioning
confidence: 97%
“…They were more successful when they fit the equation to the runner's data. 31 At minimum, best practice requires estimating an individualized τ W′ for each athlete, in their specific mode of exercise. 22,23,27,30 The method of calculation of the integral has important implications for model behavior.…”
Section: The W′ Bal Modelsmentioning
confidence: 99%